Variables and Challenges in Assessing EU Experts’ Performance - Cathrine Holst; Silje H. Tørnblad (Politics and Governance, 2015)
Expert advice in political processes is supposed to improve decisions. If expertise fails in this function, a legitimacy problem occurs: granting political power to experts may be defensible, but only on the grounds that it contributes to enlightening political processes and facilitate problem-solving. The paper provides a theoretical exploration of four variables that are key when assessing the epistemic quality of expert deliberations: the degree to which these deliberations are 1) informed by technical expertise, 2) regulated by epistemically optimal respect and inclusion norms, 3) focused on politically relevant and applicable knowledge, and 4) approaching questions involving moral judgment and standard setting competently. Previous research on the European Commission’s use of expert advice has more or less overlooked the question of experts’ epistemic performance, and this paper discusses the possible reasons for this in light of well-known methodological challenges in studies of elite behaviour; access and bias problems. A discussion of the merits and limitations of different available data on the Commission experts shows that the biggest obstacle in the study of experts’ epistemic performance is rather the problem of epistemic asymmetry, i.e. of how researchers as non-experts can assess the epistemic quality of experts’ contributions and behaviour. The paper offers, finally, a set of strategies to get research going despite this problem.